A role for the nuclear receptor NR2F6 in peritoneal B cell homeostasis - Olson, William J.; Jakic, Bojana; Labi, Verena; Woelk, Johannes; Derudder, Emmanuel; Baier, Gottfried; Hermann-Kleiter, Natascha (Frontiers in Immunology, 2022)
B cells are key mediators of humoral immunity. Mature B cells fall into various sub-classes that can be separated by their ontogeny, expression of cell surface markers, anatomical location, and function. B1 subsets play important roles in natural immunity and constitute the majority of B cells in newborns. In the adult, B1 cells predominate in the pleural and peritoneal cavities, while the mature B2 follicular subset makes up the major fraction of B cells in lymphoid tissue, although important subsets of antibody-secreting B1 cells are also present at these sites. B1 cells are the main producers of natural IgM but can also contribute to elimination of some pathogens, while B2 cells primarily mediate response to foreign antigens. The differential molecular underpinning of the B1 and B2 subsets remains incompletely understood. Here we demonstrate that germline-deficiency of the orphan nuclear receptor NR2F6 causes a partial loss of B1b and B2 B cells in the peritoneum while leaving peritoneal B1a cells unaltered. A competitive bone marrow chimera in Nr2f6+/+ host mice produced normal numbers of peritoneal B1b and B2 cells. The proliferation of Nr2f6-/- peritoneal B cells was not altered, while the migration marker CXCR5 was reduced on all subsets but Beta7-integrin was reduced only on peritoneal B1b and B2 cells. Similarly, B1b and B2 but not B1a cells, exhibited significantly reduced survival.